Take a Holistic Approach to Control Nitrification. Issue 12 (5th December 2019) - Sun, Yue; Cook, Nicholas
Abstract : In tackling a nitrification problem at a Texas municipal water utility, results of a sampling study led to implementing a holistic strategy to improve operations, monitoring, and infrastructure.